Pathological Assessment of the AJCC Tumor Regression Grading System After Preoperative Chemoradiotherapy for Chinese Locally Advanced Rectal Cancer. Issue 3 (January 2016) - Zhang, Lu-Ning; Xiao, Wei-Wei; Xi, Shao-Yan; OuYang, Pu-Yun; You, Kai-Yun; Zeng, Zhi-Fan; Ding, Pei-Rong; Zhang, Hui-Zhong; Pan, Zhi-Zhong; Xu, Rui-Hua; Gao, Yuan-Hong
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: We used American Joint Committee on Cancer (AJCC) Staging Manual system to assess the prognostic significance of tumor regression grading (TRG) for locally advanced rectal cancer (LARC) (T3/4 or N+) patients who were treated with preoperative chemoradiotherapy (CRT). The 4 AJCC-TRG classifications were evaluated on surgical specimens from 295 LARC patients receiving CRT. Overall survival (OS), disease-free survival (DFS), local recurrence-free survival (LRFS), and distant metastasis-free survival (DMFS) were estimated using Kaplan–Meier method and Cox regression model. Classifications of TRG 0, 1, 2, and 3 were found in 27.5%, 19.3%, 45.7%, and 7.5% of the resected specimens, respectively. Three-year OS was 95.5% for TRG0, 91.5% for TRG1, 84.8% for TRG2, and 85.7% for TRG3 ( P  = 0.035). Three-year DFS was 89.0% for TRG0, 74.4% for TRG1, 70.9% for TRG2, and 62% for TRG3 ( P  = 0.018). By multivariate analysis, AJCC-TRG ( P  = 0.033), residual lymph node metastasis (ypN+) ( P  < 0.001) and pretreatment CA19-9 level ( P  = 0.035) were significant predictors of OS. Pathological T category ( P  = 0.006) and nodal status ( P  < 0.001) after CRT were the most important independent prognostic factors for DFS. AJCC-TRG is a prognostic factor for LARC patients receiving CRT, independent of pathological staging.